Increasing the Availability and Consumption of Drinking Water in Middle Schools: A Pilot Study - Patel, Anisha I. (Centers for Disease Control and Prevention, 2011)
INTRODUCTION: Although several studies suggest that drinking water may help prevent obesity, no US studies have examined the effect of school drinking water provision and promotion on student beverage intake. We assessed the acceptability, feasibility, and outcomes of a school-based intervention to improve drinking water consumption among adolescents. METHODS: The 5-week program, conducted in a Los Angeles middle school in 2008, consisted of providing cold, filtered drinking water in cafeterias; distributing reusable water bottles to students and staff; conducting school promotional activities; and providing education. Self-reported consumption of water, nondiet soda, sports drinks, and 100% fruit juice was assessed by conducting surveys among students (n = 876), preintervention and at 1 week and 2 months postintervention, from the intervention school and the comparison school. Daily water (in gallons) distributed in the cafeteria during the intervention was recorded. RESULTS: After adjusting for sociodemographic characteristics and baseline intake of water at school, the odds of drinking water at school were higher for students at the intervention school than students at the comparison school. Students from the intervention school had higher adjusted odds of drinking water from fountains and from reusable water bottles at school than students from the comparison school. Intervention effects for other beverages were not significant. CONCLUSION: Provision of filtered, chilled drinking water in school cafeterias coupled with promotion and education is associated with increased consumption of drinking water at school. A randomized controlled trial is necessary to assess the intervention's influence on students' consumption of water and sugar-sweetened beverages, as well as obesity-related outcomes.